Sejarah Sosial dan Intelektual Masyarakat Muslim Andalusia dan Kontribusinya bagi Peradaban Dunia - Yoyo Hambali (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
Using a socio-historical approach, this paper aims to describe the history of social and intellectual of Spanish (Andalusian) Moslems, since its natal, advance, and decay. The conclusion of this paper shows that Islam, in the Medieval Europe, has taken root in Spain. How was the Spain Islam established? What are the rudiments that created Andalus cultivated through centuries? However, why thence it experienced disintegration, ruined and disappeared? Even though Andalus has vanished, Muslims of Spain has their contribution for the European and Western countries, and the world civilization in general.